Cohort profile: follow-up of a Berlin Aging Study II (BASE-II) subsample as part of the GendAge study - Ilja Demuth; Verena Banszerus; Johanna Drewelies; Sandra Düzel; Ute Seeland; Dominik Spira; Esther Tse; Julian Braun; Elisabeth Steinhagen-Thiessen; Lars Bertram; Andreas Thiel; Ulman Lindenberger; et al. (BMJ Open, 2021)
Purpose: The study 'Sex- and gender-sensitive prevention of cardiovascular and metabolic disease in older adults in Germany', the GendAge study, focuses on major risk factors for cardiovascular and metabolic diseases and on the development of major outcomes from intermediate phenotypes in the context of sex and gender differences. It is based on a follow-up examination of a subsample (older group) of the Berlin Aging Study II (BASE-II). Participants: The GendAge study assessments took place between 22 June 2018 and 10 March 2020. A total of 1100 participants (older BASE-II subsample, aged ≥65 years) with baseline data assessed at least by one of the BASE-II partner sites were investigated in the follow-up. These participants had a mean age of 75.6 years (SD ±3.8), with a mean follow-up at 7.4 years (SD ±1.5). Findings to date: Data from different domains such as internal medicine, geriatrics, immunology and psychology were collected, with a focus on cardiometabolic diseases and in the context of sex and gender differences. Diabetes mellitus type 2 was reported by 15.6% and 8.6% of men and women, respectively. In contrast, this disease was diagnosed in 20.7% of men and 13.3% of women, indicating that a substantial proportion of almost 30% was unaware of the disease. Echocardiography revealed that left ventricular ejection fraction was higher in women than in men, in agreement with previous reports. Future plans: A gender questionnaire assessing sociocultural aspects implemented as part of the follow-up described here will allow to calculate a gender score and its evaluation based on the newly collected data. At the same time, the other BASE-II research foci established over the past 10 years will be continued and strengthened by the BASE-II transition into a longitudinal study with follow-up data on the older subsample. Trial registration number: DRKS00016157.
Keywords: 330